Extremophiles as a Model of a Natural Ecosystem: Transcriptional Coordination of Genes Reveals Distinct Selective Responses of Plants Under Climate Change Scenarios - Bajay, Stephanie K.; Cruz, Mariana V.; da Silva, Carla C.; Murad, Natália F.; Brandão, Marcelo M.; de Souza, Anete P. (Frontiers in Plant Science, 2018)
The goal of this research was to generate networks of co-expressed genes to explore the genomic responses of Rhizophora mangle L. populations to contrasting environments and to use gene network analysis to investigate their capacity for adaptation in the face of historical and future perturbations and climatic changes. RNA sequencing data were generated for R. mangle samples collected under field conditions from contrasting climate zones in the equatorial and subtropical regions of Brazil. A gene co-expression network was constructed using Pearson’s correlation coefficient, showing correlations among 78,364 transcriptionally coordinated genes. Each region exhibited two distinct network profiles; genes correlated with the oxidative stress response showed higher relative expression levels in subtropical samples than in equatorial samples, whereas genes correlated with the hyperosmotic salinity response, heat response and UV response had higher expression levels in the equatorial samples than in the subtropical samples. In total, 992 clusters had enriched ontology terms, which suggests that R. mangle is under higher stress in the equatorial region than in the subtropical region. Increased heat may thus pose a substantial risk to species diversity at the center of its distribution range in the Americas. This study, which was performed using trees in natural field conditions, allowed us to associate the specific responses of genes previously described in controlled environments with their responses to the local habitat where the species occurs. The study reveals the effects of contrasting environments on gene expression in R. mangle, shedding light on the different abiotic variables that may contribute to the genetic divergence previously described for the species through the use of simple sequence repeats (SSRs). These effects may result from two fundamental processes in evolution, namely, phenotypic plasticity and natural selection.